Features of modeling in agricultural production with risks - Kuzubov Alexey; Maksimenko Aleksandr; Sapozhnikova Ekaterina; Malinina Olga (BIO Web of Conferences, 2024)
For the modern economy, the agricultural sector is an important link. In a market economy, agricultural management processes have become significantly more complex, as they develop under conditions of uncertainty. This leads to the need to take into account not only traditional factors of economic activity, but also supply and demand for agricultural products, weather conditions, which largely determine the economic efficiency of the agricultural sector. The uncertainty inherent in the agro-industrial complex is the main difficulty in scientific research into the structural and functional organization of this complex. Uncertainty is generated by many factors, the most important for agricultural production are weather and market conditions, scientific and technological progress. The need to take into account and manage weather risk arises from the objective requirements of a market economy, which requires enterprises to find ways to better adapt to external and internal conditions of operation and development of production. Agricultural production is constantly being reformed in market conditions. In this regard, there is a need to develop new methodological approaches to planning the safety and development of agricultural enterprises, associations and the agro-industrial complex as a whole. The study of these issues is possible through the use of economic-mathematical modeling and computers. The article discusses the concept of planning the use and development of agricultural enterprises under conditions of uncertainty. The concept is based on the development of organizational, economic and methodological approaches to the formation of the planning process, which provides agricultural enterprises with the prerequisites for better adaptation of production in conditions of weather risk, increasing the competitive level of enterprise sustainability.